The Dis1/Stu2/XMAP215 Family Gene FgStu2 Is Involved in Vegetative Growth, Morphology, Sexual and Asexual Reproduction, Pathogenicity and DON Production of Fusarium graminearum - Zhu, Yuanye; Zhang, Yuanshuai; Liu, Na; Ren, Weichao; Hou, Yiping; Duan, Yabing; Song, Xiushi; Zhou, Mingguo (Frontiers in Microbiology, 2020)
The conserved Dis1/Stu2/XMAP215 microtubule association proteins (MAPs) family plays an important role in microtubule dynamics, nucleation and kinetochore-microtubule attachments. However, function of Dis1/Stu2/XMAP215 homologue in plant pathogenic fungi has not been determined. Here, we identified and investigated the Dis1/Stu2/XMAP215 homologue (FGSG_10528) in Fusarium graminearum (FgStu2p). Co-localization experiment and co-immunoprecipitation (Co-IP) assay demonstrated that FgStu2p is a microtubule associated protein. Besides, FgStu2 could also interact with Fgγ-tubulin and presumed FgNdc80, which suggested that the FgStu2 gene might associate with microtubule nucleation and kinetochore-microtubule attachments like Dis1/Stu2/XMAP215 homologues in other species. Moreover, the FgStu2 promoter replacement mutants (FgStu2-Si mutants) produced twisted hyphae and decreased growth rate. Microscope examination further showed that the microtubule polymerization was reduced in FgStu2-Si mutants, which could account for the aberrant morphology. Although the microtubule polymerization was affected in FgStu2-Si mutants, the FgStu2-Si mutants didn’t show highly increased sensitivity to anti-microtubule fungicide carbendazim (methyl benzimidazol-2-ylcarbamate [MBC]). In addition, the FgStu2-Si mutants exhibited curved conidia, decreased number of conidial production, blocked ability of perithecia production, decreased pathogenicity and deoxynivalenol (DON) production. Taken together, these results indicate that the FgStu2 gene plays a crucial role in vegetative growth, morphology, sexual reproduction, asexual reproduction, virulence and deoxynivalenol (DON) production of F. graminearum, which brings new insights into the functions of Dis1/Stu2/XMAP215 homologue in plant pathogenic fungi.